Efficacity of Gefitinib or Erlotinib for EGFR- mutant advanced non-small cell lung carcinoma - عبدالله نادر (Latakia University Journal -Medical Sciences Series, 2022)
tyrosine kinase inhibitors (TKIs) targeting the Epithelial growth factor receptor(EGFR) have fundamentally changed the treatment of metastatic NSCLC. Gefitinib and erlotinib are first-generation EGFR-TKIs that have been shown to be effective in the treatment of EGFR mutation-positive, metastatic non-small-cell lung cancer compared with chemotherapy in all treatment lines. This retrospective study aims to evaluate the efficacy of these two drugs in patients with metastatic non-small cell lung cancer (NSCLC) who are EGFR mutation positive in terms of Disease-free survival. The study included 46 patients who attended the chemotherapy and radiotherapy center from November 2016 to December 2020 who had metastatic non-small cell lung cancer positive for EGFR mutation. All patients were treated with one of the tow drugs gefitinib or erlotinib or sometimes alternately depending on the availability of drugs. The mean survival rate without recurrence, regardless of the treatment line, was 6.95 months (1-27 months) We found a better response when using drugs as a first line, where the average disease-free survival rate was 12.4 months (5-27 months). while the average in the second line was 6.32 months (1-17 months), and the average in the third line and beyond was 3.30 months (1-6) months. Increased efficacy was observed in non-smokers with a statistically significant difference, while this difference was not statistically significant according to gender, age and histological type. Tyrosine kinase inhibitors (gefitinib and erlotinib) have very significant efficacy in EGFR-positive, metastatic NSCLC, especially when given as first-line therapy.